EFFECT OF FINANCE ACT 2019 ON TAX REVENUE IN NIGERIA (Journal of the Management Sciences, 2024)
The paper examines the effect of finance Act 2019 on tax revenues in Nigeria. The study was guided by three specific objectives which include to determine the Pre and Post effect of removal of flat rate of 30% on Companies Income Tax (CIT) revenue in Nigeria, to examine the Pre and Post effect of 25% increase in Value Added Tax (VAT) revenue in Nigeria and to analyze the Pre and Post effect of 10% withholding tax on dividend payout on the Petroleum Profit Tax (PPT) revenue in Nigeria.Wilcoxon Statistical Test Tool was developed to test the linear relationship between the dependent and independent variables. The result of the analysis reveals that the adoption of Finance Act 2019 has significant and positive effect on Companies Income Tax (CIT) and Value Added Tax (VAT) revenues in Nigeria. It also shows that 10% withholding tax on dividend payout on the Petroleum Profit Tax has significant effect on (PPT) revenue in Nigeria. The study concludes that adoption of Finance Act 2019 has significant effect on CIT, VAT and PPT revenues in Nigeria. The paper therefore recommends that tax revenue should be adequately shared to be beneficial to every taxpayer in order to motivate them pay their taxes as and when due. Finally, Federal Inland Revenue Service (FIRS) and state internal services should engage on high sensitization especially amongst the growing Small and Medium Enterprises (SMEs) on the importance and civic obligations to pay tax since they have little knowledge of their tax obligations.
Keywords: Finance Act 2019, Company income tax, Value added tax, Petroleum profit tax